Hubungan Antara kadar Vitamin D dengan HbA1c pada Pasien Diabetes Mellitus Tipe 2 di Laboratorium Klinik Thamrin Medan Tahun 2019 - Desi Novita; Meida Nugrahalia; Ida Fauziah (Universitas Medan Area, 2020)
Vitamin D as an immunomodulator play an important role in controlling glycemic levels and reducing the risk of diabetes. HbA1c as a substance formed from glucose binding with hemoglobin which has a good relationship with average blood sugar levels of fasting, daily and 3 months. This research was conducted to determine the relationship between vitamin D levels and HbA1c in patients with type 2 diabetes mellitus. This research used descriptive methods and the research samples were all patients who suffer from type 2 diabetes mellitus in the clinical laboratory of Thamrin Medan. Data were obtained by checking vitamin D and HbA1c levels in patients blood serum. The number of samples in this research were 47 people. The results of this research indicate that there is a very weak relationship between vitamin D levels and HbA1c, with r = 0,225 and R = 5,1%, therefore, it was clearly presented that effect of vitamin D on HbA1c is 5,1%.